LAJU EROSI DAN SEDIMENTASI DAERAH ALIRAN SUNGAI RAWA JOMBOR DENGAN MODEL USLE DAN SDR UNTUK PENGELOLAAN DANAU BERKELANJUTAN - Wibowo, Ariyanto; Soeprobowati, Tri Retnaningsih; Sudarno, Sudarno (Indonesian Journal of Conservation, 2015)
Rawa Jombor which located in Klaten have 3 (three) watershed as channels of water in the swamp. These watersheds are Kali Danguran Bajing Watersheds, Kali Gebyok Watersheds and Kali Jayan Watersheds. The existence of the three watersheds that passes through residential areas and agriculture in the suspect may cause sedimentation and increased fertility in Rawa Jombor. To predict rate of sedimentation on each watershed in the Rawa Jombor needed a soil erosion prediction and sedimentation models. One of model that often used is the USLE model. This research aim is to determine decrease of the function of the environment in Rawa Jombor measured from erosion and sedimentation parameters and their impact on Rawa Jombor. This research uses the USLE models to predict soil erosion and Sediment Delivery Ratio (SDR) model toÂ predict sediment results with the help of software ArcGIS 10.1. The results of both models obtained value erosion in the Kali Danguran Bajing watershed of 15892.39 tonnes / year, Kali Gebyok watershed of 8972.29 tons / year, and Kali Jayan watershed of 5142.95 tonnes/year. Estimation of sediment in the watershed Danguran Bajing is at 3996.94 tons / year, the watershed Gebyok of 2621.70 tons / year, while the Jayan at 1812.37 tons / year.Â Rawa Jombor terletak di Kabupaten Klaten memiliki 3 (tiga) DAS sebagai saluran masuknya air pada rawa. Ketiga DAS tersebut adalah DAS Kali Danguran Bajing, DAS Kali Gebyok, dan DAS Kali Jayan. Ketiga DAS tersebut melewati daerah permukiman dan pertanian di duga dapat menyebabkan sedimentasi dan peningkatan kesuburan pada Rawa Jombor. Untuk memprediksi laju sedimentasi pada tiap â tiap DAS di Rawa Jombor diperlukan suatu model pemrediksi erosi tanah dan model sedimentasi. Salah satu model yang sering digunakan adalah model USLE. Tujuan penelitian ini adalah untuk mengetahui penurunan nilai fungsi lingkungan Daerah Aliran Sungai di Rawa Jombor diukur dari parameter erosi dan sedimentasi dan dampaknya terhadap Rawa Jombor. Penelitian ini menggunakan model USLE untuk prediksi erosi tanah dan model Sediment Delivery Ratio (SDR) untuk prediksi hasil sedimen dengan menggunakan bantuan software ArcGIS 10.1. Hasil dari kedua model tersebut didapatkan nilai erosi pada DAS Kali Danguran Bajing sebesar 15.892,39 ton/tahun, DAS Kali Gebyok sebesar 8972,29 ton/tahun, dan DAS Kali Jayan sebesar 5142,95 ton/tahun. Perkiraan hasil sedimen pada DAS Danguran Bajing adalah sebesar 3.996,94 ton/tahun, pada DAS Gebyok sebesar 2.621,70 ton/tahun, sedangkan DAS Jayan sebesarÂ 1.812,37 ton/tahun.Â